(untitled) (Asian Journal of Law and Humanity, 2026)
Despite Indonesia’s constitutional guarantees regarding the right to health, local governments frequently face structural obstacles when implementing universal healthcare mandates at the grassroots level. This study analyses the strategic efforts of the Pekalongan Regency Government in fulfilling the right to health for underprivileged communities under Regent Regulation (Perbup) No. 6 of 2020 and evaluates the socio-legal implications of administrative failures within the local health insurance distribution system. Adopting a socio-legal approach with qualitative methods, empirical data were gathered through interviews with the Pekalongan Regency Health Office, Social Affairs Office, and underprivileged families, complemented by an analysis of regional socio-economic indicators. The study reveals that whilst Pekalongan Regency achieved a nominal Universal Health Coverage (UHC) rate of 99.67%, a data disparity exists. Approximately 40% of health infrastructure in remote areas remains deficient, and thousands of impoverished beneficiaries experience unilateral, unnotified deactivation of their local government-funded health insurance (PBI APBD) due to poor inter-agency database synchronisation. The implementation of Regent Regulation No. 6 of 2020 satisfies formal legal certainty but fails to deliver substantive justice due to bureaucratic inertia and structural data paralysis. This study recommends a paradigm shift towards an Integrated Fiduciary Data System to prevent ongoing neglect of civil rights